Image-Guided Liver Mapping Using Fluorescence Navigation System with Indocyanine Green for Anatomical Hepatic Resection - Aoki, Takeshi; Yasuda, Daisuke; Shimizu, Yoshinori; Odaira, Masanori; Niiya, Takashi; Kusano, Tomokazu; Mitamura, Keitaro; Hayashi, Ken; Murai, Noriyuki; Koizumi, Tomotake; Kato, Hirohisa; Enami, Yuta; et al. (World journal of surgery, 2008)
Background In malignant hepatic neoplasm, anatomic resection could improve survival and limit complications from hepatectomy. Our purpose was to develop an intraoperative method for identifying segment and subsegment of the liver with high-sensitivity near-infrared fluorescence imaging. Methods The subjects were 35 patients with hepatic malignant liver disease who received hepatectomy in 2006. The segments of liver method of identification that used infrared observation camera system termed Photo Dynamic Eye-2 (PDE-2) with indocianine green (ICG) for the patient with malignant liver tumor (hepatocellular carcinoma: 13 cases; metastatic liver cancer: 18 cases; intrahepatic cholangio carcinoma: 4 cases) were performed before liver resection. Results Although greenish stain of the liver surface after the injection of ICG via portal vein is not visible clearly without infrared observation camera system PDE-2, 1 minute after injection of ICG with fluorescent using infrared observation camera system PDE-2, demarcation of liver segment and subsegment was clearly detected. Ten minutes after injection of ICG with fluorescent using infrared observation camera system PDE-2, fluorescence of liver subsegment remained. Stained subsegment and segment of liver were identifiable in 33 (94.3%) of the 35 patients. There were no complications or side-effects related to the injection of patent blue dye. Conclusion We demonstrated here that near-infrared fluorescence imaging system is a novel and reliable intraoperative technique to identify hepatic segment and subsegment for anatomical hepatic resection.